2016
DOI: 10.3390/molecules21030374
|View full text |Cite
|
Sign up to set email alerts
|

Compound Library Screening Identified Cardiac Glycoside Digitoxin as an Effective Growth Inhibitor of Gefitinib-Resistant Non-Small Cell Lung Cancer via Downregulation of α-Tubulin and Inhibition of Microtubule Formation

Abstract: Non-small-cell lung cancer (NSCLC) dominates over 85% of all lung cancer cases. Epidermal growth factor receptor (EGFR) activating mutation is a common situation in NSCLC. In the clinic, molecular-targeting with Gefitinib as a tyrosine kinase inhibitor (TKI) for EGFR downstream signaling is initially effective. However, drug resistance frequently happens due to additional mutation on EGFR, such as substitution from threonine to methionine at amino acid position 790 (T790M). In this study, we screened a traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…Other investigators have demonstrated that cardiac glycosides have distinct effects on the regulation of Ca 2+ levels and apoptosis in human fibroblasts and cancer cells, which is in line with the results of our study 45 . Compared with other cardiac glycosides, the CC 50 of P.A is 50% of that of Digoxin in A549s, almost 10% of that of Digoxin in H1975s 46 , and less than the CC 50 of Digitoxin in both EGFR-related cell lines 18 . However, P.A.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other investigators have demonstrated that cardiac glycosides have distinct effects on the regulation of Ca 2+ levels and apoptosis in human fibroblasts and cancer cells, which is in line with the results of our study 45 . Compared with other cardiac glycosides, the CC 50 of P.A is 50% of that of Digoxin in A549s, almost 10% of that of Digoxin in H1975s 46 , and less than the CC 50 of Digitoxin in both EGFR-related cell lines 18 . However, P.A.…”
Section: Discussionmentioning
confidence: 86%
“…The clinical applications of Artemisinin in the treatment of malaria and Berberine in the treatment of type II diabetes aroused research interests regarding TCM 17 . In our previous studies, we screened a library of 800 natural compounds using MTT assays and identified Proscillaridin A (P.A) as having a relatively large anti-cancer effect in A549 and H1975 NSCLC cell lines 18 . In this study, we aimed to further investigate the mechanism of action of P.A, a constituent of squill- Drimia maritima , as a treatment for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic effect of digitoxin in NSCLC H1975 cells is caused by G2 phase arrest in cells resistant to tyrosine kinase inhibitors. Digitoxin overcomes tyrosine kinase inhibitor resistance and decreases cell growth via a mechanism dependent on α-tubulin expression and disruption of microtubule polymerization [ 127 ].…”
Section: Role Of Na/k-atpase In the Lungmentioning
confidence: 99%
“…The incidence and mortality of lung cancer is the highest among all malignant tumors worldwide; it is a disease that severely threatens human health and affects quality of life (1,2). Non-small cell lung cancer (NSCLC) accounts for ~80% of all lung cancer cases.…”
Section: Introductionmentioning
confidence: 99%